A case report: Cleistanthus collinus (Oduvan) poisoning - Joseph, Jimmy; Henry, Renoy A. (International Journal of Advances in Medicine, 2025)
Cleistanthus collinus-an extremely toxic plant has been reported to be used for deliberate self-harm in different parts of the country, notably South India. Toxins contained include Cleistanthin A and B arediphyllin derivatives and are known to cause neuromuscular blockade, type 2 respiratory failure, type 2 renal tubular acidosis, hypokalaemia, cardiac arrhythmias. We are presenting a case report where the poisoning was associated with type 2 respiratory failure, acute kidney injury, type 2 renal tubular acidosis, hypokalaemia, acute respiratory distress syndrome. The patient was managed with intravenous N-acetylcysteine, ventilatory support and multiple sessions of dialysis following which the patient after a prolonged stay of 29 days was discharged from the hospital.